Nanofabrication for nanophotonics - Yang, Younghwan; Kwon, Hyunah; Fischer, Peer (ACS nano, 2025)
Nanofabrication, a pivotal technology at the intersection of nanoscale engineering and high-resolution patterning, has substantially advanced over recent decades. This technology enables the creation of nanopatterns on substrates crucial for developing nanophotonic devices and other applications in diverse fields including electronics and biosciences. Here, this mega-review comprehensively explores various facets of nanofabrication focusing on its application in nanophotonics. It delves into high-resolution techniques like focused ion beam and electron beam lithography, methods for 3D complex structure fabrication, scalable manufacturing approaches, and material compatibility considerations. Special attention is given to emerging trends such as the utilization of two-photon lithography for 3D structures and advanced materials like phase change substances and 2D materials with excitonic properties. By highlighting these advancements, the review aims to provide insights into the ongoing evolution of nanofabrication, encouraging further research and application in creating functional nanostructures. This work encapsulates critical developments and future perspectives, offering a detailed narrative on the state-of-the-art in nanofabrication tailored for both new researchers and seasoned experts in the field.
Gesehen am 14.10.2025